Creative Industries Development in Russia: Tendencies and Perspectives - PATLASOV, Oleg; ZHAROV, Yerzhan (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).30, 2018)
Development of creative industries in Russia shall be reviewed as one of possible options for shifting from economy with raw materials dependence and raising the competitiveness of the national economy. So in relation to this, the significance is granted to the analysis of the main pre-conditions and conditions for development of creative industries, for evaluation of the potential of creative industries development in Russian and preparation of set of actions to be taken to develop creative industries. The article provides the analysis of the contemporary state and tendencies of developing creative industries in Russia; there were factors revealed, which suspended creative industries development in Russia, and the proposals were made for actions and mechanisms, required for sustainable development of creative industries in Russia. Additionally, within the frames of the research a sociological interview was arranged, which demonstrated the level of creative industries development in general and specifically for its types.